2001
DOI: 10.1017/s0317167100001165
|View full text |Cite
|
Sign up to set email alerts
|

The Recognition, Assessment and Management of Dementing Disorders: Conclusions from the Canadian Consensus Conference on Dementia

Abstract: To develop evidence based consensus statements on which to build clinical practice guidelines for primary care physicians towards the recognition, assessment and management of dementing disorders; ii) to disseminate and evaluate the impact of these statements and guidelines built on these statements. O p t i o n s : Structured approach to assessment, including recommended laboratory tests, choices for neuroimaging and referral; management of complications (especially behaviour problems and depression) and use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0
10

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(138 citation statements)
references
References 105 publications
3
125
0
10
Order By: Relevance
“…In contrast to the APA Guidelines, they noted that the evidence for the clinical use of Gingko biloba, vitamin E, and selegiline was "inconclusive." Third, in June 1999, the Canadian Consensus Conference on Dementia published the guidelines that were more far-reaching, comprehensive, and comprised several pharmacologic recommendations (89). When present, physicians should treat vascular risk factors, including arterial hypertension, hypercholesterolemia, diabetes mellitus, smoking, use of anticoagulation for atrial fibrillation, and secondary prevention of transient ischemic attacks (TIAs) and stroke.…”
Section: Clinical Practice Guidelinesmentioning
confidence: 99%
“…In contrast to the APA Guidelines, they noted that the evidence for the clinical use of Gingko biloba, vitamin E, and selegiline was "inconclusive." Third, in June 1999, the Canadian Consensus Conference on Dementia published the guidelines that were more far-reaching, comprehensive, and comprised several pharmacologic recommendations (89). When present, physicians should treat vascular risk factors, including arterial hypertension, hypercholesterolemia, diabetes mellitus, smoking, use of anticoagulation for atrial fibrillation, and secondary prevention of transient ischemic attacks (TIAs) and stroke.…”
Section: Clinical Practice Guidelinesmentioning
confidence: 99%
“…The 1989 CCCAD 124 had originally suggested that in primary care settings such neuroimaging could be limited to atypical cases delineated using clear guidelines, and these guidelines on referral for neuroimaging were again adopted with modification at the second CCCD conference in 1998. 135 The most commonly used modality -computed tomography (CT) has a clear role in excluding rare reversible causes of dementia such as brain tumor or NPH but it is unclear that CT can distinguish AD or cortical dementias from normal aging. Since excluding treatable pathology is its major indicator, a noncontrast CT is adequate in most cases.…”
Section: Neuroimagingmentioning
confidence: 99%
“…Four sources of increased stress on neurologists and geriatricians are worth noting: 1) the number of elderly, memory-impaired individuals continue to rise 30 and yet a "wait and see" approach is less acceptable to patients now that symptomatic treatment for AD exists, 2) physicians are being instructed to draw diagnostic distinctions they might previously have ignored (e.g. MCI vs AD), 3) time-consuming assessment of MSE and functional assessment are being encouraged as an essential component of diagnostic assessment without any concomitant financial remuneration for the physician involved, and 4) on one hand, authorities such as the second Canadian Consensus Conference on Dementia 135 insist that the initial assessment of dementia (and its treatment) should take place in a family practice setting, while on the other hand, there are serious pressures afoot that will result in increasing numbers of memory-impaired individuals being referred to neurologists and geriatricians for diagnosis and treatment. In addition to those factors already listed, one would add pressures to obtain neuroimaging more rapidly and new complex provincial government forms required for obtaining donepezil (and ultimately other effective medications) under government/insurance programs.…”
Section: Who Should Diagnose Dementiaand What Should We Diagnose?mentioning
confidence: 99%
“…Referred to as responsive behaviours, behavioural and psychological symptoms can include aggression, disruptive behaviours, disinhibition, apathy, depression, anxiety and agitation (Cerejeira et al 2012;Patterson et al 1999;Savva et al 2009). These behaviours are a means of communication and reflect a response to something in the person's environment (Cohen-Mansfield 2000; Kunik et al 2010).…”
Section: Introductionmentioning
confidence: 99%